MODEL MULTILITERASI KRITIS DALAM PEMBELAJARAN SISWA SEKOLAH DASAR (Jurnal Pendidikan Dasar, 2019)
Abstract : The critical multiliteracy model always involves students to be active in asking questions or making their own conclusions. Through challenging multiliteracy learning students are expected to be able to have confidence, be smart, communicative, brave and have character. In this study using the literature review method. Based on the results of the research conducted, critical multiliteracy models mostly show success in the learning process and learning outcomes. Keywords : Critical multiliteracy, elementary school students